The mediating role of innovation on enabling and coercive control in enhancing HEIs performance - Farwitawati, Reni; Ismail, Tubagus; Hanifah, Imam Abu; Indriana, Ina (Journal of Accounting and Investment, 2025)
Research aims: In a competitive environment, leaders of higher education institutions (HEIs) must adopt strategies to enhance performance. This study examines the role of management control systems (MCS) in fostering innovation to improve HEIs performance.Design/Methodology/Approach: Using a quantitative approach, data were collected through surveys from 210 lecturers at private HEIs in Indonesia, employing random sampling techniques. Hypothesis testing was conducted using partial least squares structural equation modeling (PLS-SEM).Research findings: The results reveal that MCS, encompassing both enabling and coercive control, significantly enhances higher education performance. Additionally, innovation was found to impact performance positively. The results also showed that innovation mediated the relationship between MCS implementation and performance improvement, suggesting that supportive leadership and constructive feedback from leaders not only encourage innovation but also contribute to improving overall organizational outcomes.Theoretical contribution/Originality: This study is among the first to conceptualize MCS through the dual lenses of enabling and coercive control as a catalyst for innovation in higher education. Integrating management control theory with innovation-driven performance frameworks it contributes to both academic discourse and practical HEIs governance.Research limitation/Implication: A key limitation is the focus solely on private higher education. Future research should compare private and public higher education, as differing organizational cultures and regulations may influence control system effectiveness and innovation. The findings offer theoretical insights into the relationship between MCS, innovation, and performance in higher education while also providing practical guidance for higher education managers in designing effective strategies.